Two new species and a new combination in Pleroma (Melastomataceae) from the Brazilian Atlantic Forest - Schmitz Meyer, Fabrício; Moreno Arantes, Fabíula; Goldenberg, Renato (Phytotaxa, 2024)
Pleroma littorale is a new species described from several specimens collected in the Brazilian states of São Paulo, Paraná and Santa Catarina. It is morphologically similar to Pleroma urvilleanum, but differs by the cucullate bracteoles, with the apex obtuse and covering the flower bud (vs. ovate, with the apex acute and not covering the flower bud), and sepals with an obtuse apex (vs. attenuate). Pleroma semisterile is a new species described from six specimens collected in Pancas, state of Espírito Santo. It is morphologically similar to Pleroma fontanae, but differs by the longer petioles, 19–51.3 mm long (vs. 3.3–12.6 mm long), the antepetalous stamens with pedoconective and appendages covered by glandular trichomes (vs. glabrous), and narrower fruits, 5.5–6 mm wide (vs. 8.1–8.9 mm). One remarkable feature of the latter species is the androecium with apparently well-formed antesepalous stamens that do not produce pollen and are consequently staminoidal. This character has not been previously mentioned for species in Pleroma, but it may have been overlooked in species that are morphologically related to P. semisterile, such as P. fontanae, P. magdalenense, and P. manicatum. Finally, we also present the new combination Pleroma magdalenense, for a species originally described under Tibouchina that has been treated as a synonym of P. heteromallum.